Biomechanical and biochemical evaluation of the effect of systemic application of omeprazole on the osseointegration of titanium implants - Tekin, Samet; Dundar, Serkan; Demirci, Fatih; Bozoglan, Alihan; Yildirim, Tuba Talo; Gunes, Nedim; Ozcan, Erhan Cahit (Springer Japan Kk, 2021)
Background This study aimed to investigate the effects of systemic omeprazole treatment on the osseointegration of titanium implants. Material and methods After surgical insertion of titanium implants into the metaphyseal part of rats' both right and left tibial bones, the animals were randomly divided into three equal groups: control (n = 8), omeprazole dosage-1 (n = 8) (OME-1), and omeprazole dosage-2 (n = 8) (OME-2) and totally 48 implants were surgically integrated. The rats in the control group received no treatment during the four-week postoperative experimental period. In the OME-1 and OME-2 groups, the rats received omeprazole in doses of 5 and 10 mg/kg, respectively, every 3 days for 4 weeks. After the experimental period, the rats were euthanized. One rat died in each group and the study was completed with seven rats in each group. Blood serum was collected for biochemical analysis, and the implants and surrounding bone tissue were used for biomechanical reverse-torque analysis. In the biomechanical analysis, implants that were not properly placed and were not osseointegrated were excluded from the evaluation. Results One-way analysis of variance and Tukey's honestly significant difference test and Student's t test were used for statistical analysis. The reverse-torque test (control (n = 9), OME-1 (N = 7), and OME-2 (n = 7)) analysis of biochemical parameters (alkaline phosphatase, calcium, phosphorus, aspartate aminotransferase, alanine amino transferase, urea, and creatinine) revealed no significant differences between the groups (control (n = 7), OME-1 (N = 7), and OME-2 (n = 7)) (P > 0.05). Conclusions Omeprazole had no biomechanical or biochemical effects on the osseointegration process of titanium implants.
Keywords: Osseointegration; Proton pump inhibitors; Omeprazole; Bone implant connection; Bone implant contact